Integrated Research for Integrated Ocean Management - Rölfer, Lena; Liconti, Arianna; Prinz, Natalie; Klöcker, Clara Antonia (Frontiers in Marine Science, 2021)
With the start of the United Nations Decade of Ocean Science for Sustainable Development in 2021, research priorities to support the sustainable use of coastal and ocean resources and their conservation is in the spotlight. However, to date comprehensive regulation and management of multifaceted and often poorly understood ecosystems, such as the deep sea, has proven challenging. This is partly due to the complexity of coastal and ocean social-ecological systems, which are shaped by interactions between biophysical ecosystem processes and anthropogenic pressures, and at different geographical and temporal scales and administrative levels. In order to address the challenges posed by often-conflicting interests between economic activities and nature conservation at areas both national and beyond national jurisdiction, there is an urgent need for integrated approaches that bridge the gap between science, policy and practice. Consequently, the interest in multi, inter- and transdisciplinary research approaches at the national and international levels has been growing. This review will provide an overview of current shortcomings in coastal and ocean management and highlight project examples for incorporating inter- and trans-disciplinary approaches in the research design. From the project examples we identify challenges and good-practices in integrated research. Common subjects include addressing complexity, strengthening knowledge exchange, sustaining funding, increasing communication, ensuring policy relevance and involving the public. Based on this we propose key considerations for an integrated research design that is aimed at the effective translation between science, policy and society in support of sustainable coastal and ocean governance.